The Relationship Between Parenting Patterns And Self Confidence In Children Under Five - Sri Wahyuni; Irma M. Yahya (Jurnal EduHealth, 2023)
The family has a very important role in every stage of the development of family members. Toodlers 0-5 years is a golden age or golden age to form the foundations of personality, intelligence, skills, and sociability. Self confidence is an important part of a teenagerʼs life. According to Rohayati (2011), self confidence is a important source in toddlerhood because they become individuals who are able to control many aspects of themselves and set goals that lead to success. The purpose of this study is ti find out the relationship of parenting with self confidence in toddlers in Tumupa Satu Subdistrict Tuminting Manado City.Research uses quantitative methods using correlation research methods, which are methods that aim to determine the relationship between two variables. The time approach used is the cross sectional approach. The sample of respondent was as many as 40 people using sampling tercniques, namely the total sample. Data collection using questionnaire sheets, analyzed by Chy Square statistical test.The results of the most age research 26-35 years 26 respondents (65.0%), the most high school education 28 respondents (70.0%), the most jobs of housewives 26 respondents (65.0%). Chi Square test results obtained a p value of 0,001 where < α 0,05. The conclusion in this study is that there is a relationship of the parenting with Self Confidence in toddlers in Tumumpa Village Tuminting District Manado City. Advice is expected with the research, it is hoped that respondents can find out good parenting for child development.